Zirconium-Catalyzed Reaction of 1-Alkynyl Sulfides with Et3Al: A Novel Route to Trisubstituted 1-Alkenyl Sulfides - Kadikova, Rita N.; Ramazanov, Ilfir R.; Vyatkin, Alexey V.; Dzhemilev, Usein M. (Synlett, 2018)
The reaction of 1-alkynyl sulfides and alkynyl sulfoxides with Et3Al under zirconocene catalysis conditions has been studied. The interaction between 1-alkynyl sulfides and Et3Al in the presence of catalytic amounts of Cp2ZrCl2 leads to trisubstituted 1-alkenyl sulfides in moderate to good yields (56–73%) with high regioselectivity and stereoselectivity. 1-Alkynyl sulfoxides, upon treatment with Et3Al under the same reaction conditions, undergoes reduction to give sulfides. The excess of Et3Al (7 equiv) in this reaction causes cyclic carboalumination of in situ generated 1-alkynyl sulfide to form trisubstituted 1-alkenyl sulfides in quantitative yield.
Keywords: 1-alkynyl sulfides; 1-alkynyl sulfoxides; zirconocene catalysis; 1-alkenyl sulfides; cyclic carboalumination